EFFECT OF DELONIX REGIA LEAF EXTRACT ON GLUCOSE TOLERANCE IN GLUCOSE-INDUCED HYPERGLYCEMIC MICE - Rahman, M.; Hasan, N.; Das, A. K.; Hossain, T.; Jahan, R.; Khantun, A.; Rahmatullah, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Delonix regia (Fabaceae) leaf is used in folk medicine of Bangladesh for the treatment of diabetes, but so far no scientific study has been done which may support its use in traditional medicine. The present study was carried out to evaluate the possible glucose tolerance efficacy of methanolic extract of Delonix regia leaf using glucose-induced hyperglycemic mice. The extract at different doses was administered one hr prior to glucose administration and blood glucose level was measured after two hrs of glucose administration (p.o.) using glucose oxidase method. The statistical data indicated significant oral hypoglycemic activity on glucose-loaded mice at every dose. Maximum anti-hyperglycemic activity was showed at 400 mg/kg which was comparable to that of a standard drug, glibenclamide (10 mg/kg). The methanolic extract of leaf of Delonix regia had beneficial effects in reducing the elevated blood glucose level of hyperglycemic mice.